2021
DOI: 10.21203/rs.3.rs-622770/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Deciphering the interactions of SARS-CoV-2 proteins with human ion channels using machine learning-based method

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is responsible for the worldwide COVID-19 pandemic which began in 2019. It has a high transmission rate and pathogenicity leading to health emergencies and economic crisis. Recent studies pertaining to the understanding of the molecular pathogenesis of SARS-CoV-2 infection exhibited the indispensable role of ion channels in viral infection inside the host. Moreover, machine learning (ML)-based algorithms are providing higher accuracy for host-SARS-Co… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 94 publications
(107 reference statements)
0
1
0
Order By: Relevance
“…Various studies determined CoV proteins modulating host signaling pathways through the interactions with host proteins (Khan and Islam 2021;Munjal et al 2021). Particularly, studies have shown that activation of intracellular signaling cascades induced upon SARS-CoV infection leads to the post-translational modifications (PTMs) and activation of downstream molecules (Garrington and Johnson 1999;Kyriakis and Avruch 2001;Whitmarsh and Davis 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Various studies determined CoV proteins modulating host signaling pathways through the interactions with host proteins (Khan and Islam 2021;Munjal et al 2021). Particularly, studies have shown that activation of intracellular signaling cascades induced upon SARS-CoV infection leads to the post-translational modifications (PTMs) and activation of downstream molecules (Garrington and Johnson 1999;Kyriakis and Avruch 2001;Whitmarsh and Davis 2000).…”
Section: Introductionmentioning
confidence: 99%